Structural and mineralogical mapping using multispectral satellite data (Aster, Landsat 8 OLI, and Sentinel 2B) combined with field work in the Western High Atlas, Morocco - Elbakhouch, Nouhaila; Ibouh, Hassan; Touil, Ahmed; Chafiki, Driss (Geologos, 2024)
The Tighardine area in the Western High Atlas Massif is composed of rocks ranging in age from Neoproterozoic to Cenozoic. The area is intensely deformed with a multidirectional diversity of faults and also hosts a polymetallic ore deposit (Tighardine mine) and prospects of significant economic value, some of which are related to fault structures. In order to identify favourable areas of mineral deposition, structural and mineralogical mapping using satellite images was conducted in this region. For this purpose, various remote sensing approaches were employed on images from Landsat 8 OLI, Sentinel 2 and ASTER sensors. The process started with lineament extraction methods so as to identify faults manually from satellite images. Principal component analysis (PCA) and the optimal indexing factor (OIF) were used to achieve good discrimination of lithological units. Additionally, several band ratios were applied to ASTER, Landsat 8 OLI and Sentinel 2, in order to derive multiple maps corresponding to hydrothermal alteration zones. Analysis of the results from the obtained maps and their overlay with field data has allowed us to: (i) identify three main structural orientations. The most frequent and longest is the NE–SW direction, which coincides with the principal mineralised horizon of the Tighardine deposit. Results suggest an extension of this horizon towards the south-west at the Ait Zitoune and towards the west in the Ait Hsayn region. Two new fault set has been identified by remote sensing: NW-SE fracture, generally of Mesozoic-Cenozoic age, and an E-W fractures trend, particularly developed in the Neoproterozoic basement and considered of Ediacaran age; (ii) highlighting two potential mineralisation zones: in the Ediacaran basement, revealing alterations of silica, dolomite, clay minerals, iron oxide and alunite-kaolinite-pyrophyllite, hosting the main mineralisation axis (Tighardine mine); in the northern part corresponding to the overthrust zones of Cambrian onto Cenozoic formations.